THE EFFECT OF E-SERVICE QUALITY, BRAND IMAGE, AND BUSINESS ETHICS ON SHOPEE CUSTOMER SATISFACTION AMONG ACCOUNTING STUDENTS (A STUDY OF ACCOUNTING STUDENTS AT UNP KEDIRI) - Yogi Ardi; Puji Astuti; Mar'atus Solikah (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : This study aims to analyze the influence of e-service quality, brand image, and business ethics on Shopee customer satisfaction among accounting students at Universitas Nusantara PGRI Kediri Design/Methode/Approach : A quantitative approach was employed, with data collected through questionnaires from 44 accounting students using purposive sampling. Data analysis included multiple linear regression, validity and reliability tests, and hypothesis testing Research Finding : The results indicate that e-service quality (security, communication, reliability, responsiveness), brand image (corporate, user, and product image), and business ethics (transparency, fairness) significantly influence customer satisfaction. Theoretical contribution/Originality : This study contributes to the existing literature by integrating three critical factors—e-service quality, brand image, and business ethics—into a single framework to analyze their impact on customer satisfaction in the context of e-commerce. Practitionel/Policy implication : Shopee should prioritize improving e-service quality, strengthening brand image, and adhering to ethical business practices to enhance customer satisfaction Research limitation : This study focuses on e-service quality, brand image, and business ethics as independent variables, and consumer satisfaction as the dependent variable. This study was conducted on accounting students of Nusantara PGRI Kediri University who used the Shopee platform.